Mengembangkan Berpikir Kreatif Matematis melalui Pembelajaran Brainstorming-Based Learning: Studi Pra-Eksperimen pada Pendidikan Menengah Islam - Wahyuni Wahyuni (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
Mathematics instruction that is predominantly oriented toward procedural problem-solving often provides limited opportunities for students to develop mathematical creative thinking. This condition highlights the need for learning strategies that encourage idea generation, multiple solution pathways, and meaningful mathematical exploration. The present study investigated the effectiveness of brainstorming-based learning in fostering students' mathematical creative thinking on the topic of functions within the context of Islamic secondary education. A quantitative approach was employed using a pre-experimental one-group pretest-posttest design involving 24 eighth-grade students from a Madrasah Tsanawiyah in Langsa, Indonesia. Mathematical creative thinking was assessed through an essay test developed based on four indicators: fluency, flexibility, originality, and elaboration. The collected data were analyzed using descriptive statistics, a paired-sample t-test, and normalized gain (N-Gain) analysis. The findings revealed a substantial improvement in students' average scores, increasing from 38.00 on the pretest to 80.00 on the posttest, with an N-Gain value of 0.68, indicating a moderate level of improvement. Statistical analysis further confirmed a significant difference between pretest and posttest performance (t(23) = 13.24, p < 0.001). These findings suggest that brainstorming-based learning effectively promotes mathematical creative thinking by encouraging collaborative discussion, divergent thinking, and the exploration of multiple problem-solving strategies. Therefore, this instructional approach offers a promising alternative for strengthening students' mathematical creativity in Islamic secondary education.